Deprotonation, insertion and isomerisation in the post-functionalisation of tris-pyridyl aluminates. Issue 17 (10th April 2019) - Plajer, Alex J.; Kopf, Sara; Colebatch, Annie L.; Bond, Andrew D.; Wright, Dominic S.; García-Rodríguez, Raúl
Abstract : Reactions of aluminate anions [EtAl(6-R-2-py)3 ] − (6-R-2-py = 6-R-2-pyridyl, R = Me or Br) with aldehydes (RCHO) or carboxylic acids (RCO2 H) reveal how these species can be used to sense chirality and show a new aspect of isomerism in this area. Abstract : Post-functionalisation of the aluminate anion [EtAl(6-R-2-py)3 ] − (6-R-2-py = 6-R-2-pyridyl, R = Me or Br) can be accomplished via nucleophilic addition of the pyridyl groups to the electrophilic CO group of aldehydes (RCHO) or by deprotonation of carboxylic acids (RCO2 H). NMR spectroscopic and crystallographic studies show how 6-Me-2-py groups can detect chirality and reveal a new aspect of isomerism.